The Stakeholder Consultation Workshop Report: Transforming the Rules of the Game: Gendered Livability in Peri-urban Dhaka - International Potato Center (International Potato Center, 2023)
Urban space is highly unequal, gendered, and divided. Urban policy and development planning often overlook the issue of food and water security for the most marginalized populations, who are often unregistered and considered as ‘temporary’ residents. In Bangladesh, the rural-urban migration of women is increasingly common. However, research on gender, food and water security in agricultural organizations often focuses on rural contexts where food is produced.